Pengendalian Kualitas Hasil Produksi “Sus Tenun Lintau” dengan Menggunakan Analisis Capability Process - Susriyati; Mutiara Yetrina (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2025)
Sus Tenun Lintau (STL) is an MSME that produces woven clothing materials, detta, and scarves. The most popular at the moment is detta. In order to compete in the market, STL sets high standards by using an effective and efficient production system. The accuracy of homogeneous products must have the same character. From the background, this study analyzes the quality of STL production results. This study uses capability process analysis. capability process can identify the quality of production (product nonconformity) produced, analyze the capability of the production quality process and control the quality of production results. The results of processing, interpretation of dimensional characteristic data are spread following a normal distribution while the control limits indicate that the dimensional characteristics of the detta product variables are in control. From the results of the Capability Process calculation, the process capability (Cp) can be analyzed, the value of 1.00 <Cp <1.33 and the characteristic value of Cp = Cpk, this means that the process is centered in the middle between the specification limits. The result is that the production capability (process capability) of each product size dimension has good results